Government and Community Efforts to Address the Problems of Intolerance, Radicalism and Terrorism in Indonesia - Nathearia; Didik Himmawan; Amelia Putri Syariah (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
The purpose of this study is to identify the strategies implemented by the Indonesian government and the role of society in preventing and addressing issues of intolerance, radicalism, and terrorism. The research method used in this article is a descriptive-analytical approach with a literature study, involving data collection from policy documents, scientific articles, books, and reports relevant to the discussed issues. The findings of this study indicate that the Indonesian government has undertaken various efforts to combat intolerance, radicalism, and terrorism through security policies, education, and deradicalization programs. Some of the measures include strengthening regulations, enhancing the capacity of security forces, and collaborating with international organizations. Additionally, society has actively contributed to preventing radicalism through multicultural education, interfaith dialogue, and social activities that strengthen relationships among citizens. Despite these efforts, significant challenges remain, such as the presence of groups exposed to radicalization and a lack of understanding of tolerance in certain segments of society. Therefore, further collaboration between the government and society is essential to create a more inclusive and peaceful Indonesia.